2006
DOI: 10.1039/b610573d
|View full text |Cite
|
Sign up to set email alerts
|

Particle-size effect of nanoscale platinum catalysts in oxygen reduction reaction: an electrochemical and 195Pt EC-NMR study

Abstract: Oxygen reduction reaction (ORR) measurements and (195)Pt electrochemical nuclear magnetic resonance (EC-NMR) spectroscopy were combined to study a series of carbon-supported platinum nanoparticle electrocatalysts (Pt/CB) with average diameters in the range of roughly 1-5 nm. ORR rate constants and H(2)O(2) yields evaluated from hydrodynamic voltammograms did not show any particle size dependency. The apparent activation energy of 37 kJ mol(-1), obtained for the ORR rate constant, was identical to that obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
167
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 191 publications
(175 citation statements)
references
References 40 publications
7
167
0
1
Order By: Relevance
“…39 We have demonstrated that the ORR rate constant (k app , per unit ECA), its activation energy, and P(H 2 O 2 ) in O 2 -saturated 0.1 M HClO 4 were all independent of d Pt from Pt 1.6nm /CB to bulk-Pt at 30 to 50°C, as well as from Pt 2.6nm /CB to bulk-Pt up to 110°C. 40 It was also found that the smallest (Pt 1.6nm ) particles agglomerated at higher temperatures (² 60°C). This result led our research to the second important issue regarding the Pt particle-size effect on the durability.…”
Section: ¹1mentioning
confidence: 90%
See 3 more Smart Citations
“…39 We have demonstrated that the ORR rate constant (k app , per unit ECA), its activation energy, and P(H 2 O 2 ) in O 2 -saturated 0.1 M HClO 4 were all independent of d Pt from Pt 1.6nm /CB to bulk-Pt at 30 to 50°C, as well as from Pt 2.6nm /CB to bulk-Pt up to 110°C. 40 It was also found that the smallest (Pt 1.6nm ) particles agglomerated at higher temperatures (² 60°C). This result led our research to the second important issue regarding the Pt particle-size effect on the durability.…”
Section: ¹1mentioning
confidence: 90%
“…Recently, non-fluorinated hydrocarbon (HC) electrolyte membranes have been developed to reduce cost, to elevate the operating temperature, and to avoid environmental pollution due to fluoride on disposal. Specifically, the elevation of operating temperature (² 100°C) leads to a significant cost reduction by increases in the MA values for the ORR 40 of the cathode catalysts and the CO-tolerant HOR of the anode catalysts, 36,55 together with a down-sizing of the heat exchanger (radiator) in FCVs (due to increased ¦T ).…”
Section: Cathode Catalyst Layers With Sulfonated Hydrocarbonmentioning
confidence: 99%
See 2 more Smart Citations
“…The reaction on carbon supported Pt is practically H2O specific in acid conditions [124], although the presence of Nafion can slightly increase H2O2 production to a percent most likely as a result of sulfonate interactions [125]. In alkali, a few percent of H2O2…”
mentioning
confidence: 99%